Respuestas

2012-03-16T01:15:57+01:00

 , aplicada a  x^2+5x+6=0

a representa a la parte literal del ´primer termino b al segungo c al tercero resolvamos

x=-5+raiz de (5)^2-4(1)(6)

     _________________________

                 2(1)

X=5+raiz 25-24

    _____________                 segunda respuesta

          2

X=5+raiz 1                                                       x=5-1

    ___                                                                  __________

          2                                                                2

X=5+1

    _____________                                 x=4/2

          2    

x=6/2                                                      x=2

x=3